Honey Therapy to Reduce the Frequency of Diarrhea in Children - Darah Ifalahma; Mehru Nisha; Nikhen Sinky Pramudita (Proceedings of the International Conference on Nursing and Health Sciences, 2023)
Diarrhea has an impact on children's health, one of which is dehydration. Laboratory studies and clinical trials, pure honey has bactericidal activity that causes diarrhea. Giving honey is useful in reducing the frequency of diarrhea in children. Honey has antibacterial, anti-inflammatory and antiviral properties that can treat diarrhea. This study aims to determine the effectiveness of honey to reduce the frequency of diarrhea in children. The design of this study was a quasi-experimental pretest and posttest nonequivalent without a control group. The research sample was 20 children who experienced diarrhea. Honey is given 3 times a day as much as 5 ml. Results: The results showed that the frequency of diarrhea decreased after being given honey, which means that there was an effect of giving honey on a decrease in the frequency of diarrhea in children (p<0.001). Conclusions: Honey can be used as an alternative therapy to reduce the frequency of diarrhea in children.